Immigrants' experiences of qualifications recognition and employment : results from the Prototype Longitudinal Survey of Immigrants to Australia (LSIA) - Iredale, Robyn R. (Australian Govt. Pub. Service, 1995)
The study analyses the Prototype Longitudinal Survey of Immigrants to Australia (PLISA) data.The data used in the study is obtained from a sample of 765 people aged 15 years and over including 446 people who immigrated to Sydney, Melbourne and Adelaide over the period from June to December 1991.